Identification of Cementing Quality and Hydraulic Seal at Hydrocarbon Zone in F Field - Ratnayu Sitaresmi; Faradiba Faradiba; Puri Wijayanti (Penerbitan Universitas Trisakti, 2020)
Cement analysis needs to be done on wells that have decreased production and there is additional water production. The longer the well is produced, the water will approach and even reach the perforation zone which results in the water being produced. Several steps must be proposed in knowing and handling water production in wells, in addition to collecting data from wells and reservoirs in full, analysis of problems related to mechanics such as cementing analysis needs to be done to determine the possibility of leakage, microannulus or channeling. The method used is quantitative, by comparing the amount of water production in two wells and its relation to the hydraulic seal formed in the cement. The analysis was carried out on two wells, namely F-3 and F-4. F-3 wells produce large amounts of water, namely 1168 BWPD. This is possible considering the position of this well adjacent to the water zone. And based on the analysis carried out, the hydraulic seal on the F-3 well has not yet been formed making it possible for direct contact between the productive zone and the water zone. Water production in F-4 wells is 35 BWPD. The low water production in these wells can also be assumed due to the formation of hydraulic seals in cementing. Looking at the data above, it can be concluded that without the formation of hydraulic seals on the F-3 wells, secondary cementing needs to be done to close the cementing which is not good so that there is no leakage anymore and there is no communication between the productive zone and the water zone.